Influences on hospital admission for asthma in south Asian and white adults: qualitative interview study - Chris Griffiths; Gurpreet Kaur; Madeleine Gantley; Gene Feder; Susan Hillier; J. R. Goddard; G.E. Packe (2001)
Abstract Objective: To explore reasons for increased risk of hospital admission among south Asian patients with asthma. Design: Qualitative interview study using modified critical incident technique and framework analysis. Setting: Newham, east London, a deprived area with a large mixed south Asian population. Participants: 58 south Asian and white adults with asthma (49 admitted to hospital with asthma, 9 not admitted); 17 general practitioners; 5 accident and emergency doctors; 2 out of hours general practitioners; 1 asthma specialist nurse. Main outcome measures: Patients9 and health professionals9 views on influences on admission, events leading to admission, general practices9 organisation and asthma strategies, doctor-patient relationship, and cultural attitudes to asthma. Results: South Asian and white patients admitted to hospital coped differently with asthma. South Asians described less confidence in controlling their asthma, were unfamiliar with the concept of preventive medication, and often expressed less confidence in their general practitioner. South Asians managed asthma exacerbations with family advocacy, without systematic changes in prophylaxis, and without systemic corticosteroids. Patients describing difficulty accessing primary care during asthma exacerbations were registered with practices with weak strategies for asthma care and were often south Asian. Patients with easy access described care suggesting partnerships with their general practitioner, had better confidence to control asthma, and were registered with practices with well developed asthma strategies that included policies for avoiding hospital admission. Conclusions: The different ways of coping with asthma exacerbations and accessing care may partly explain the increased risk of hospital admission in south Asian patients. Interventions that increase confidence to control asthma, confidence in the general practitioner, understanding of preventive treatment, and use of systemic corticosteroids in exacerbations may reduce hospital admissions. Development of more sophisticated asthma strategies by practices with better access and partnerships with patients may also achieve this. What is already known on this topic South Asian patients with asthma are at increased risk of hospital admission with asthma compared with white patients No consistent differences in severity or prevalence of asthma, prescribed drugs, or asthma education have been described, and interventions to reduce admission rates in Asian patients have met with variable success What this study adds Compared with white patients, south Asian patients admitted to hospital with asthma had less confidence to control asthma, were unfamiliar with the concept of preventive medication, and had less confidence in their general practitioners South Asian patients managed asthma attacks through family advocacy and without systematic changes in prophylaxis and without systemic corticosteroids Patients reporting difficulty in accessing primary care during attacks were often south Asian